Pemetaan Identitas Kolektif Desa Tumbu, Karangasem, Bali: Kajian Historis dan Lanskap Berdasarkan Data Prasasti dan Aturan Adat - Ni Wayan Nurwarsih; Candrayana, Kadek Windy; Utama, I Made Satria (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to map the collective identity of the people of Tumbu Village, Karangasem, Bali, using historical approaches, cultural landscape studies, and an analysis of customary rules. The primary data are sourced from 13th-century inscriptions such as the Ruk-ruk, Pasemetan, and Tumbu Puseh Inscriptions, along with awig-awig (local customary laws) that remain actively implemented. The research applies a descriptive-qualitative method through field observations, literature reviews, traditional document interpretation, and participatory interviews with community leaders and local residents. The findings reveal that the collective identity of Tumbu Village is shaped by the integration of historical values, agrarian landscapes, the Hindu-Balinese spiritual system, and a living social structure embedded in customary norms. While modernization has introduced significant changes in architecture and social structures, local communities have managed to adapt culturally without losing their traditional values. Community-based strategies have proven effective in preserving the harmony between cultural heritage and village development. The key outputs of this program include a landscape identity map, a social structure infographic, and a brief guide to customary spatial principles that may serve as a reference for village planning grounded in local wisdom. This study affirms the urgency of preserving collective identity and customary spatial systems as foundational to sustainable development in traditional Balinese villages.